Reconstruction of Indigenous Community Inclusion in Village Autonomy Policy: Towards a Substantive Autonomy Model in Indonesia - Kadaryanto, Bagio; Kurniawan, Ardian; Burhanuddin, Burhanuddin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study examines the inclusion of indigenous peoples in village autonomy policies following the enactment of the Village Law (Law No. 6 of 2014). Although the law promotes decentralization and cultural recognition, its implementation remains primarily administrative, neglecting the socio-cultural realities of indigenous communities. Only a small percentage of indigenous villages are officially recognized. At the same time, structural marginalization persists due to unequal access to resources, limited political representation, and the supremacy of national law over customary law. Using a normative legal approach, this study examines the gap between legal norms and empirical practices, drawing on primary legal materials and secondary sources, including government regulations, forestry and mining laws, research findings, and case reports. The findings suggest that the Village Law's failure lies not only in bureaucratic issues but also in the absence of structural justice and legal pluralism in policy design. Procedural and uniform autonomy fails to reflect local indigenous contexts, rendering legal recognition largely symbolic. Therefore, a shift toward substantive independence is essential, grounded in recognition, subsidiarity, and legal pluralism. This approach requires harmonization of sectoral regulations, empowerment of indigenous institutions, and fiscal reform, offering a transformative path toward more just, participatory, and inclusive village governance.